Effect on door‐to‐needle recombinant tissue plasminogen activator administration times for acute ischemic stroke with and without an emergency department pharmacist. Issue 6 (27th February 2019) - Gilbert, Brian W.; Huffman, Joel
Abstract : Study Objective: A paucity of data exists on the impact emergency department (ED) pharmacists have on a stroke team's door‐to‐needle (DTN) administration time of recombinant tissue plasminogen activator (rTPA). The purpose of this study was to assess the odds of achieving a DTN administration time for rTPA of 60 minutes or less with an ED pharmacist present. Methods: This was a retrospective, cohort study of patients who received rTPA for acute ischemic stroke (AIS) from May 2017 to May 2018. Patients were included if they were at least 18 years old and received tPA for AIS in the ED. The primary outcome for this study was the likelihood of patients receiving a DTN administration time of 60 minutes or less with or without an ED pharmacist present during a stroke alert at a primary stroke center. Results: The electronic medical record of 184 stroke alert patients was reviewed, and 65 patients were included in the final analysis. Baseline characteristics were similar in all aspects. The odds ratio was 3.3 (95% confidence interval [CI]: 1.1‐9.6; P = 0.04) to achieve a DTN administration time of 60 minutes or less when an ED pharmacist was present. The ED pharmacist present group had faster median (47 minutes vs 60 minutes; P = 0.001) and average (49 minutes vs 63 minutes; P = 0.003) DTN administration times compared with the ED pharmacist not present group. Conclusion: An ED pharmacists present during a stroke alert at our faculty resulted in reduced overall DTN rTPA administration times and increased the odds of a patient receiving rTPA less than 60 minutes from arrival for AIS. Further study is required to determine if this finding can be replicated in other EDs.